Modul Ajar Berbasis Problem Based Learning Konten Sistem Persamaan dan Pertidaksamaan Linear untuk Memfasilitasi Kemampuan Pemecahan Masalah Matematis Peserta Didik - Putri, Adela; Armis, Armis; Suanto, Elfis (Papanda, 2026)
This study aims to develop a Problem Based Learning–based teaching module on the topic of Systems of Linear Equations and Inequalities to facilitate students’ mathematical problem-solving skills, with the criteria of validity and practicality. This research is a development study employing the 4D model, which consists of Define, Design, Develop, and Disseminate stages. The development process includes several stages: (1) Define, which involves front-end analysis, learner analysis, concept analysis, task analysis, and the specification of learning objectives; (2) Design, which includes the preparation of test standards, media selection, format determination, and initial design; (3) Develop, which comprises expert validation and development trials; and (4) Disseminate, which involves the dissemination of the product through seminars and publications. The instruments used in this study were expert validation sheets to assess the validity of the teaching module and student response questionnaires to measure the practicality of the student worksheets (LKPD). The results indicate that the teaching module is valid in several aspects and meets the criteria of being very valid after revisions based on validators’ suggestions. Furthermore, the implementation of the LKPD in the small group and field test stages demonstrates that the LKPD is very practical. This is evidenced by the fact that the LKPD is easy for students to understand.